Evaluation of the response given to the vitamin D treatment in patients with osteomalacia - Genç, Selin; Genç, Ömer; Kılıçlı, Mehmet Fatih (SERNEV, 2022)
Introduction: The current study aimed to examine the relationship between 25 hydroxyvitamin D [25(OH)D] levels and demographic, clinical and laboratory parameters and response to treatment in patients living in a Central Anatolian city of Turkey and diagnosed with osteomalacia.Methods: A total of 533 patients who live in the continental climate, older than 18 years old, and have 25(OH)D levels lower than 30 ng/ml were enrolled prospectively. Patients' age, body mass index (BMI), type of clothing, season in which they were diagnosed, type of treatment and duration were recorded. At the time of diagnosis, the patients were evaluated with clinical and laboratory parameters at 1st, 2nd, and 4th months.Results: Mean serum 25(OH)D level was 7.59±4.41 ng/mL at the time of diagnosis. 25(OH)D level was 24.42±14.77 ng/ml after treatment, with severe deficiency (<10 ng/mL) in 74% of patients, deficiency (<20 ng/mL) in 24.2%, insufficiency in 1.3% (20-29.99 ng/mL). 74.4% of the women had a closed clothing style. Vitamin D levels during diagnosis and at the end of treatment did not differ according to the BMI and the diagnosis period (p> 0.05). However, as BMI increased, the response given to the treatment decreased.Conclusions: The current study showed that vitamin D deficiency is common in study population. The current findings demonstrate that treatment and follow-up should be continued until achieving normal serum 25(OH)D levels, taking into account geographic and ethnical structures to bring vitamin D levels to adequate levels.

Giriş: Bu çalışmada Türkiye’nin bir Orta Anadolu kentinde yaşayan, osteomalazi tanısı alan hastalarda 25 hidroksivitamin D [25(OH)D] düzeylerinin demografik, klinik ve laboratuvar parametreleriyle olan ilişkisi ve tedaviye yanıtının incelenmesi amaçlandı.Yöntem: Karasal iklimdeki şehirde, 25(OH)D <30 ng/ml, > 18 yaşından büyük olan 533 hasta prospektif olarak dahil edildi. Hastaların yaşı, vücut kitle indeksi (VKİ), giyim şekli, tanı aldığı mevsim, tedavi şekli ve süresi kaydedildi. Hastalar tanı anında, 1., 2. ve 4. aylarda klinik ve laboratuvar parametreleri ile değerlendirildi.Bulgular: Tanı anında ortalama serum 25(OH)D 7,59±4,41 ng/mL idi. Hastaların %74’ünde ciddi eksiklik (<10), %24,2’sinde eksiklik (<20), %1,3’ünde yetersizlik (20-29,99) olup tedavi sonrası 25(OH)D: 24,42±14,77 ng/ml idi. Kadınların %74,4’ü kapalı giyim tarzına sahipti. Tanı sırasında ve tedavi sonunda Vitamin D düzeyleri, BKİ ve tanı mevsimine göre farklılık göstermedi (p>0,05). Ancak VKİ arttıkça tedaviye verilen cevabın azaldığı bulundu.Sonuç: Bu çalışma, bölgemizde vitamin D eksikliğinin yaygın olarak görüldüğünü ortaya koymuştur. Bulgularımız D vitamini düzeyini yeterli seviyeye çıkarmak için coğrafik ve etnik yapıların da göz önünde bulundurularak, normal serum 25(OH)D düzeyine ulaşıncaya kadar tedavi ve takibe devam edilmesi gerektiğini göstermektedir.
Osteomalazili hastalarda vitamin D tedavisine verilen cevabın değerlendirilmesi
Keywords: 25-Hydroxytamin D; Osteomalacia; Vitamin D Deficiency; 25-Hidroksivitamin D; Osteomalazi; Vitamin D Yetersizliği